2019
DOI: 10.1007/s11606-019-05065-9
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Unhealthy Alcohol Use among Primary Care Patients with HIV: the Health and Motivation Randomized Clinical Trial

Abstract: BACKGROUND: Unhealthy alcohol use has adverse effects on HIV treatment. Screening, brief intervention, and referral to treatment (SBIRT) has some evidence of efficacy but may not be sufficient for those with low motivation or comorbid substance use. OBJECTIVE: To examine the effectiveness of motivational interviewing (MI) and emailed feedback (EF) among primary care HIV-positive patients, compared with treatment as usual care (UC) only, which included SBIRT. DESIGN: Randomized clinical trial. PARTICIPANTS: Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…This study examined data collected in the Health and Motivation Study, described in detail elsewhere 18. Briefly, the study was a randomised clinical trial of primary care-based behavioural interventions to reduce unhealthy alcohol use among 614 PWH in Kaiser Permanente Northern California (KPNC).…”
Section: Methodsmentioning
confidence: 99%
“…This study examined data collected in the Health and Motivation Study, described in detail elsewhere 18. Briefly, the study was a randomised clinical trial of primary care-based behavioural interventions to reduce unhealthy alcohol use among 614 PWH in Kaiser Permanente Northern California (KPNC).…”
Section: Methodsmentioning
confidence: 99%
“…Based on a systematic review of the literature and meta-analysis, Scott-Sheldon and colleagues reported in 2017 that there were only 21 studies that reported on individual-level interventions designed to address alcohol use among PWH, 71% of which were clinic-based [ 17 ]. Consistent with our approach, studies that targeted alcohol alone (vs. multiple HIV-related behaviors) and that were clinic-based (vs. recruiting from other/mixed settings), were found to be more successful at decreasing alcohol use[ 14 17 ], though these effects may vary based on baseline level of motivation and intervention strategy[ 13 ]. Building on this literature and our experiences evaluating ISAT among PWH with higher and lower levels of alcohol use[ 21 , 22 ], the current study provides additional support for approaches that include MI-based interventions that target alcohol use in clinic-based settings to promote alcohol reduction among PWH.…”
Section: Discussionmentioning
confidence: 70%
“…Such “stepped care models” allow for tailoring of treatment based on patient response while employing multidisciplinary team members as needed to deliver specific components of care to maximize resource allocation. Stepped care models have been successfully applied to a variety of medical conditions (e.g., depression, hypertension, chronic pain) [ 18 , 19 ] addressed in routine medical settings, but rarely applied to address alcohol use [ 20 ] and specifically among PWH [ 13 ]. We have recently reported the benefits of stepped alcohol treatment for PWH who have alcohol use disorder (as defined by the Diagnostic and Statistical Manual criteria to identify individuals with loss of control and adverse consequences from alcohol use) or lower levels of alcohol use in the presence of liver disease [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 614 adult HIV-positive patients in Kaiser Permanente, San Francisco, who reported prior year unhealthy alcohol use were randomized to receive either 3 sessions of (a) motivational interviewing (MI), (b) information regarding alcohol risks by emailed feedback (EF) through an EHR patient portal, or (c) usual care (UC), which included Screening, Brief Intervention, and Referral to Treatment. 1 The interventions were carried out by behavioral health specialists embedded in the primary care clinics. At 12 months all three arms reported declines in unhealthy alcohol use and alcohol related problems, with no significant differences between the groups.…”
mentioning
confidence: 99%